THE INFLUENCE OF STUDENT DISCIPLINE ON LEARNING ACHIEVEMENT: A CORRELATIONAL STUDY AMONG ELEMENTARY SCHOOL STUDENTS - Suyatmi, Sri Suyatmi; Saidah, Lilis; Yusup, Putra Yudhistira; Vitianingrum, Dian; Aditama, Mint Husen Raya (CV. TOTUS TUUS, 2025)
This study aims to analyze the relationship between student discipline and learning achievement in grade 5 elementary school students. This study uses a quantitative approach with comparative and correlational study methods that assess 31 students. The determination of the sample was carried out using the purposive sampling technique. Discipline assessment was carried out by 2 teachers and parents of students using validated instruments, while learning achievement was measured based on semester report card scores. The results of statistical analysis showed that there was a significant positive relationship between student discipline and learning achievement. The t-test score showed a significance of 0.000, which confirms the existence of a strong correlation between discipline and student learning outcomes. Although the correlation between discipline assessments from teachers and parents is not very high, the results of the study still show that students with high levels of discipline tend to have better learning achievement. These findings highlight the importance of implementing effective discipline strategies both at school and at home as an effort to improve student learning outcomes. The study concludes that discipline has an important role in shaping a conducive learning environment and supporting optimal academic achievement. The implication of this study is the need for cooperation between educators and parents in instilling discipline values from an early age to create a more qualified generation. Further research with a wider sample coverage as well as the exploration of additional factors such as motivation and learning strategies is suggested to reinforce these findings.